2020
DOI: 10.24198/mfarmasetika.v4i0.25868
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Repelan Losion Minyak Atsiri Daun Zodia (Evodia Suaveolens) Terhadap Nyamuk Aedes aegypti Linnaeus

Abstract: Zodia (Evodia suaveolens) merupakan salah satu tanaman yang mempunyai aroma yang tajam pada bagian bunga dan daunnya dan dipercaya dapat mengusir nyamuk. Daun Zodia mengandung minyak atsiri evodiamine dan rutaecarpine yang tidak disukai oleh nyamuk. Tujuan penelitian ini untuk menilai efektivitas repelen losion mengandung minyak atsiri daun Zodia pada konsentrasi 1%, 1.5% dan 2%. Metodenya dengan iosion yang dibuat dengan mencampurkan minyak atsiri hasil isolasi dari daun Zodia pada konsentrasi 1%, 1,5% dan 2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Another research suggested that zodia (Evodia Suaveolens) essential oil lotion also has a protective power for six hours at concentrations of 1%, 1.5%, and 2%. The higher the concentration, the better the protection against mosquito bites (63). This proves that the higher the concentration is used, the greater the effect has on mosquitoes.…”
Section: Observation Timementioning
confidence: 84%
“…Another research suggested that zodia (Evodia Suaveolens) essential oil lotion also has a protective power for six hours at concentrations of 1%, 1.5%, and 2%. The higher the concentration, the better the protection against mosquito bites (63). This proves that the higher the concentration is used, the greater the effect has on mosquitoes.…”
Section: Observation Timementioning
confidence: 84%